Islamic Law View Corruption as A Structured Crime (Case Study Corruption of PKH Social Assistance in Tangerang District) - Tolkah (LEGAL BRIEF, 2020)
Islamic law has a point of view in looking at corruption. Corruption is defined as a form of fraudulent practice by humans to get something, Islam has its definition, namely (risywah) something that is given to someone who has the power or position to help everything. Corruption of social assistance The family hope program is carried out by all levels so that it becomes a unity, recipients of bribes, givers of bribes and bribes. The purpose of this research is to see how Islamic law views corruption. This research approach uses qualitative with quantitative methods and primary and secondary data collection and uses literature related to Islamic law and corruption.